THE MECHANISM OF THE IMMUNE SYSTEM OF THE HUMAN BODY - O’rolboyev Navruzbek, son of Mirtoza; Daughter of Sadinova Shahnoza Farit; Umarova Zakrokhan’s daughter (Zeta Repository, 2023)
In the article, the body’s ability to fight against viruses, bacteria and fungi in the external environment, immunity and types of immunity.